2022
DOI: 10.1111/dth.15803
|View full text |Cite
|
Sign up to set email alerts
|

Switching from adalimumab originator to biosimilars in hidradenitis suppurativa: What's beyond cost‐effectiveness?

Abstract: In the last years, adalimumab biosimilars have represented a commonly used alternative to the originator agent in the treatment of moderate to severe hidradenitis suppurativa. As of today, studies investigating the switch from adalimumab originator to biosimilar, following pharmacoeconomic policies, are lacking. Herein we present a real-life setting retrospective study aimed at assessing the safety and efficacy of this switch in 37 patients, evaluated for 12 months in terms of IHS4 (International Hidradenitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
(21 reference statements)
0
9
0
2
Order By: Relevance
“…Eine weitere retrospektive Studie mit 37 Patienten untersuchte die Sicherheit und Wirksamkeit der Umstellung unter realen Bedingungen über 12 Monate anhand des IHS4 und des HiSCR 403 . Insgesamt zeigten sich keine signifikanten Unterschiede zwischen dem Originalpräparat von Adalimumab und dem Biosimilar in Bezug auf das klinische Ansprechen.…”
Section: Therapieunclassified
“…Eine weitere retrospektive Studie mit 37 Patienten untersuchte die Sicherheit und Wirksamkeit der Umstellung unter realen Bedingungen über 12 Monate anhand des IHS4 und des HiSCR 403 . Insgesamt zeigten sich keine signifikanten Unterschiede zwischen dem Originalpräparat von Adalimumab und dem Biosimilar in Bezug auf das klinische Ansprechen.…”
Section: Therapieunclassified
“…Roccuzzo et al 31 recently presented a retrospective real-world study designed to evaluate the safety and efficacy of switching from adalimumab originator to biosimilars in 37 patients, evaluated for 12 months in terms of IHS4 (International Hidradenitis Suppurativa Severity Score System) and HiSCR. Overall, no significant differences emerged between originator and biosimilar adalimumab in terms of clinical response following nonmedical switch.…”
Section: Adalimumabmentioning
confidence: 99%
“…Overall, no significant differences emerged between originator and biosimilar adalimumab in terms of clinical response following nonmedical switch. 31 …”
Section: Adalimumabmentioning
confidence: 99%
“…Several studies have demonstrated the bioequivalence and similar safety profiles of the adalimumab biosimilars compared to the originator agent [ 122 , 123 ]. However, a loss of treatment efficacy has been observed after switching from adalimumab originator to biosimilars in clinical studies [ 124 , 125 , 126 ]. Kirsten et al evaluated the clinical responses of 94 patients after switching from adalimumab originator to biosimilar ABP 501, and reported a loss of response or new onset of adverse events in 33.3% [ 127 ].…”
Section: Treatmentmentioning
confidence: 99%